The double path of light in ancient times: Lessons for Science Educational Practice - JoaquÃƒÂn Vidal-LÃƒÂ³pez (International Journal of Theory and Application in Elementary and Secondary School Education, 2020)
The light has been part of myths, scientific explanations, and theories of mind from the origin of mankind. In this concern to explain cosmogony detached from the gods, the ancient Greeks began to seek the foundation of primordial matter from which it derives everything that exists. In this work are explained some approaches to the study of light from the first religious traditions, some Greek authors (Plato, Democritus, and Euclid), one medieval author (Grosseteste), and the last developments in the study of light carried out in the last century.This work is shown how a physical concept as light can be understood from a wide variety of perspectives along centuries and cultures. The actual knowledge of light, based on Einstein's Relativity Theory and Quantum Physics, is also explained. At the end of this work is exposed to one reflection about how myths and rational explanations are always combined for explaining natural events, and how both paths are valuable because they have different characteristics and purposes.Both mythical and rational perspectives coexist today in our society. They have different purposes, advantages and limitations. This approach is very useful for Primary and Secondary Science students, because it helps them to know the development of a key concept of physics (light) that is still revised today.